Is Oligotrophy an Equalizing Factor Driving Microplankton Species Functional Diversity Within Agulhas Rings? - Cesar-Ribeiro, Caio; Piedras, Fernanda R.; da Cunha, Leticia C.; de Lima, Domênica T.; Pinho, Luana Q.; Moser, Gleyci A. O. (Frontiers in Marine Science, 2020)
From the southwestern termination of the Agulhas current, anticyclonic eddies are emitted and drift across the South Atlantic Ocean. This study is based on a FORSA cruise, from Cape Town to Arraial do Cabo in June 2015, during which three eddies of different ages (E1, seven months; E3, eleven months; E5, twenty-four months) from the Agulhas current were sampled for microplankton identification and determination of functional traits. The stations where sampling occurred at each eddy included a control outside the eddy and three stations inside the eddy — border, midway, and center. Functional traits were determined based on microscopic observations and consultation of the literature. An evident decay in the Agulhas eddies towards the west was observed, and each eddy proved to be different. E1 represented a younger and more robust structure while the other eddies, E3 and E5, were more alike with similar physical, chemical, and ecological characteristics and almost identical functional strategies, demonstrating that although their species compositions were different, the strategies used by the species were the same. The most crucial ecological trait for microplankton was nutrition mode. The microplankton contained mainly mixotrophic dinoflagellates and cyanobacteria adapted to oligotrophic conditions. The functional strategy of microplankton did not differ among the eddies and stations, with mixotrophy being the most striking trait. Therefore, the microplankton communities of the eddies fits the theory of neutrality, whereby species perform similar ecological functions. Even with the species composition being different in each eddy and/or within the same eddy, the functional strategy was the same, with scarce resources and species selected that best use any source of nutrients or use evolutionary advantages to live in an oligotrophic environment.